2008
DOI: 10.1073/pnas.0802412105
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary linkage between eukaryotic cytokinesis and chloroplast division by dynamin proteins

Abstract: Chloroplasts have evolved from a cyanobacterial endosymbiont and been retained for more than 1 billion years by coordinated chloroplast division in multiplying eukaryotic cells. Chloroplast division is performed by ring structures at the division site, encompassing both the inside and the outside of the two envelopes. A part of the division machinery is derived from the cyanobacterial cytokinetic activity based on the FtsZ protein. In contrast, other parts of the division machinery involve proteins specific to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 36 publications
3
100
0
Order By: Relevance
“…This revealed that the cytokinetic dynamins were monophyletic (LMN: 88% bootstrap support), and represented a sister group to the chloroplast division dynamins (PQR: 43% bootstrap support). The last common ancestor of amoebozoans and archaeplastids therefore had a class C cytokinetic dynamin (LMN) (22) that persists essentially unchanged in many lineages, as well as another class C dynamin of unknown sequence (???) (Fig.…”
Section: Entire Ancestral Dynamin Variants Are Preserved In Extant Spmentioning
confidence: 99%
“…This revealed that the cytokinetic dynamins were monophyletic (LMN: 88% bootstrap support), and represented a sister group to the chloroplast division dynamins (PQR: 43% bootstrap support). The last common ancestor of amoebozoans and archaeplastids therefore had a class C cytokinetic dynamin (LMN) (22) that persists essentially unchanged in many lineages, as well as another class C dynamin of unknown sequence (???) (Fig.…”
Section: Entire Ancestral Dynamin Variants Are Preserved In Extant Spmentioning
confidence: 99%
“…Finally, DYNAMIN-RELATED PROTEIN5B (DRP5B; also known as ARC5), a member of the dynamin family of self-assembling proteins, is recruited by PDV1 and PDV2 to chloroplasts to complete chloroplast division (Miyagishima et al, 2006). DRP5B is specific to plants and algae and is thought to have evolved from a dynamin-related protein involved in eukaryotic cytokinesis (Miyagishima et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Because the Dnm1 is continuously expressed throughout the cell cycle, including organelle division cycles in C. merolae (27,28), an unknown factor that can recruit Dnm1 molecules to the division sites may play a role for the key regulator in the divisions of peroxisome and mitochondrion. Although the dynamin family members are phylogenetically grouped according to their functions, Dnm1 is grouped in the same subclade of DRP3s, which have dual functions (29,30). Thus, serial control of peroxisomal division and mitochondrial division by the same dynamin might be conserved among virtually all eukaryotes.…”
Section: Function Of the Pod Machinery And Comparisons Between The Podmentioning
confidence: 99%